Music information seeking behaviour as motivator for musical creativity. Issue 5 (14th September 2015) - Lavranos, Charilaos; Kostagiolas, Petros A.; Martzoukou, Konstantina; Papadatos, Joseph
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the connection between musicians' information seeking behaviour and the creative process in music, providing a framework for understanding the role of information needs satisfaction in musical creativity. A number of studies in information science literature have been carried out attempting to model cognitive, affective, behavioural and contextual factors associated with music information seeking behaviour. However, only few studies have addressed the relationship between information seeking behaviour and musical creative activities such as composition, performance and improvisation, listening and analysis. Design/methodology/approach – The focus of this paper is to provide a framework for the study of information seeking behaviour for the purposes of satisfying musical creativity information needs, combining the theoretical basis of an established model of information behaviour developed by Wilson and the theoretical perspectives of a music creative thinking model proposed by Webster. The key features of the two models are synthesized in a unified model of information seeking behaviour for musical creativity and enriched with research findings identified in the literature of both musical information seeking and musical creativity. Findings – The proposed conceptual framework offers an integrated interpretation of the combinations of information needs, information resources and environmental/personal barriers, which enable musical creativity. In the authors' approach "musical creativity" is treated as a musician's aim or ambition or drive for expression and is influenced by the way musicians seek information for that purpose. Therefore, musical creativity is an intentional behaviour which acts as motivator for information seeking and is affected by the available information and the musician's information seeking profile. The current study include three important findings: first, the design and development of music library and information services for musical creativity; second, the development of music information literacy skills for creativity; and third, the information seeking behavioural perspective for universal musical creativity, and the implications for cultural musical heritage diffusion around the world. Originality/value – An integrated information seeking behaviour model which includes musical creativity is developed through the synthesis of two already existing approaches, that of Wilson for information seeking behaviour and that of Webster for creative thinking in music. The present conceptual study presents a three stage pattern or process for modelling information seeking for musical creativity: the process initiates with the intention-motivation for creativity, then proceeds to information seeking behaviour and then concludes with the musical creativity outcomes. This is the first study that seeks to understand the relationships between creativity and information seeking behaviour.